2013
DOI: 10.1016/j.future.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient distributed monitoring with active Collaborative Prediction

Abstract: Isolating users from the inevitable faults in large distributed systems is critical to Quality of Experience. We formulate the problem of probe selection for fault prediction based on end-to-end probing as a Collaborative Prediction (CP) problem. On an extensive experimental dataset from the EGI grid, the combination of the Maximum Margin Matrix Factorization approach to CP and Active Learning shows excellent performance, reducing the number of probes typically by 80% to 90%. Comparison with other Collaborativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The goal of this paper is very different: the contribution of SMF and SMFA is on the focus on smarter, data-driven sampling schemes for the case where historical information is available. Rish and Tesauro [2007] proposed a method to handle fault inference based on a collaborative prediction approach, further analyzed in Feng et al [2013]. Although this method significantly reduces the number of required probes for acquiring an accurate view of the system, it is somehow static.…”
Section: Matrix Factorization For Fault Predictionmentioning
confidence: 99%
See 3 more Smart Citations
“…The goal of this paper is very different: the contribution of SMF and SMFA is on the focus on smarter, data-driven sampling schemes for the case where historical information is available. Rish and Tesauro [2007] proposed a method to handle fault inference based on a collaborative prediction approach, further analyzed in Feng et al [2013]. Although this method significantly reduces the number of required probes for acquiring an accurate view of the system, it is somehow static.…”
Section: Matrix Factorization For Fault Predictionmentioning
confidence: 99%
“…Rish and Tesauro [2007] integrated active learning with MMMF (min-margin heuristic) and [Feng et al 2013] have shown that active learning was a required ingredient in the most difficult and realistic case on a real-world fault prediction example. On the other hand, active learning is somehow inconvenient: because the probe selection is adaptive, it requires a feedback loop, an interface between online analysis and monitoring, and thus a more complicated software than with a predetermined setting.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work [17], inspired by [18], addressed fault prediction in a classical Collaborative Prediction framework, as a purely spatial problem where the matrix is assumed to be a snapshot of the probes outcomes. Here, we take into account the fact that the system dynamically evolves at various time scales.…”
Section: Introductionmentioning
confidence: 99%